Kesadaran Merek, Citra Merek, dan Asosiasi Merek terhadap Kepuasan Konsumen - Bambang Sutedjo; Yulia Evita Sari (Journal of Management and Bussines (JOMB), 2023)
The purpose of this study was to examine and analyze the influence of brand awareness, brand image and brand associations on customer satisfaction in a case study at Mixue Citra Grand in Semarang City. This research method is quantitative. The sample taken in this study was taken using a purposive sampling technique with the criteria of a consumer who is a student or university student who has purchased and consumed Mixue Ice Cream & Tea Citra Grand in Semarang City. Data were analyzed using validity test, reliability test, multiple regression analysis, F test, determination test (R2), and T test. The results showed, a) brand awareness on consumer satisfaction has a significance value obtained, namely 0.005 <0.05 and the value beta is 0.231 (positive); b) brand image on consumer satisfaction has a significance value obtained, namely 0.00 <0.05 and a beta value of 0.4218 (positive); c) brand association with consumer satisfaction has a significant value obtained, namely 0.001 <0.05 and a beta value of 0.276 (positive). In conclusion, brand awareness, brand image, and brand associations have a positive and significant effect on consumer satisfaction. Keywords: Brand Association, Brand Image, Consumer Satisfaction, Brand Awareness